2016
DOI: 10.1097/ccm.0000000000001623
|View full text |Cite
|
Sign up to set email alerts
|

A One-Nearest-Neighbor Approach to Identify the Original Time of Infection Using Censored Baboon Sepsis Data*

Abstract: Objective Sepsis therapies have proven to be elusive due to the difficulty of translating biologically sound and effective interventions in animal models to humans. A part of this problem originates from the fact that septic patients present at various times after the onset of sepsis while the exact time of infection is controlled in animal models. We sought to determine whether data mining longitudinal physiological data in a non-human primate model of E. coli-induced sepsis could help inform the time of onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, biomedical systems are stochastic, and incorporating randomness into clinical modeling is crucial for their validity. Zhang et al (35) attempted a "back in time" approach in a primate study using a mathematical cluster modeling technique known as "nearest Identifying core pathways in an individual is crucial for understanding septic mechanisms and applying custom therapeutic decisions.…”
Section: Using Artificial Neural Network For Enhanced Sepsis Biomarki...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, biomedical systems are stochastic, and incorporating randomness into clinical modeling is crucial for their validity. Zhang et al (35) attempted a "back in time" approach in a primate study using a mathematical cluster modeling technique known as "nearest Identifying core pathways in an individual is crucial for understanding septic mechanisms and applying custom therapeutic decisions.…”
Section: Using Artificial Neural Network For Enhanced Sepsis Biomarki...mentioning
confidence: 99%
“…However, biomedical systems are stochastic, and incorporating randomness into clinical modeling is crucial for their validity. Zhang et al (35) attempted a “back in time” approach in a primate study using a mathematical cluster modeling technique known as “nearest neighbor.” Two pig models were used to validate the methodology: one with surgically induced peritonitis and the other using an lipopolysaccharide infusion-induced approach. This study did not incorporate other immunological information in addition to biomarker assay levels.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study demonstrated that TriVote achieved very good and stable classification performances with its chosen OMIC features on both transcriptomic and methylomic datasets [62]. The Python package TriVote calculated the 10-fold cross validation classification performances of four representative binary classifiers, i.e., Nearest Neighbor (NN) [93], Support Vector Machine (SVM) [94,95], Naive Bayes (NBayes) [49,96], and Decision Tree (DTree) [97]. Both prediction accuracy and feature number are important for an OMIC-based prediction panel [37,98].…”
Section: B Binary Classification Of 5-year Survivalmentioning
confidence: 99%